Production of peptides inducing chemotaxis and lysosomal enzyme release in human neutrophils by intestinal bacteria in vitro and in vivo - Chadwick, V S; Mellor, D M; Myers, D B; Selden, A C; Keshavarzian, A; Broom, M F; Hobson, C H (Scandinavian journal of gastroenterology, 1988)
Low molecular weight (Mr 200-1500) N-formylated peptides that stimulate many leucocyte functions, including chemotaxis and lysosomal enzyme release, have previously been isolated from Escherichia coli cultures. We have used high-performance liquid chromatography and bioassay techniques to study production of such peptides by intestinal bacteria in vitro and their activity in intestinal luminal contents, obtained by in vivo dialysis methods. Bioactivity was detected in culture supernatants of all 11 species of bacteria so far investigated, was resistant to digestion with aminopeptidase, but was destroyed by carboxypeptidase, confirming that bioactive moieties were amino-terminal-blocked peptides. By similar isolation procedures, pronase-sensitive bioactive factors have been demonstrated in human rectal dialysates from normal subjects and patients with Crohn's disease. In the patients, bioactivity in dialysates was not observed after treatment with broad-spectrum poorly absorbed antibiotics. The gut may be a reservoir or source of bacterial peptides that could promote an inflammatory response should they cross the 'mucosal barrier'.